Relationship between key economic indicator, (GDP) and ISO certification take up in selected developing economies. (Nigeria,Kenya,Egypt,China and Mexico) - Owede, Tope (2011)
In an economic environment characterised in recent years by globalization and the integration of economic processes, standardization in Quality Managements Systems has had a high growth. In this context, there has been a remarkable increase in the number of certifications issued by International organizations especially to countries known and defined as “developing”. Amongst these standards, one stands out which is issued by the International Organization for standardization (ISO), this is known as the family of ISO 9000 standards. The ISO 9001 series has seen an increase in the number of certification obtained by developing countries. This adoption, gives developing countries the opportunity to compete in global market place as being ISO 9000 certified is seen as an entry qualifier into the global market place. The purpose of this study is to observe and analyze the relationship between the economies of selected developing countries and ISO take up in the selected countries (Nigeria, Kenya, Egypt, Mexico and China), with the aim of finding a possible relationship between these country‟s economic development and its ISO 9001 certification status. Having this in mind, the research employs the use of primarily quantitative techniques with some qualitative elements in order to achieve its objectives. Particularly, a linear regression analysis is run using the data collected by using Pearson‟s technique for calculating the correlation coefficient (r) and (r^2) using Microsoft excel. This particular technique for calculating correlation coefficient was chosen because it is more suitable to measure the strength and the direction of a linear relationship between two variables when ratio-typed data are used. From this study, it has been discovered that there is a linear and strong correlation between ISO certification take up in the selected developing countries across continents and their GDP which signifies the level of economic growth of countries.Also,it was discovered that the main reason why developing countries get ISO 9000 certificates is because of customer pressure and the also the ability to compete in the global market.